Adolescent Girls’ Classroom With the 8000 Days Module for Knowledge and Self-Efficacy - Sarifa Albahar; Runjati Runjati; Hermien Nugraheni (Jurnal Bidan Cerdas, 2026)
Background: Stunting is a complex health problem in Indonesia. Prevention efforts that focus only on the First 1,000 Days of Life (HPK) are often considered too late, as many adolescent girls become pregnant without optimal health preparation. The First 8,000 Days of Life (HPK) approach extends the intervention period from adolescence to early childhood. Module-based education through youth classes has the potential to enhance adolescents’ knowledge and self-efficacy as prospective parents in preventing stunting. Objective: This study aimed to determine the effect of youth classes using the First 8,000 Days of Life (HPK)module on adolescents’ knowledge and self-efficacy in stunting prevention. Methods: This quantitative study employed a quasi-experimental design with a pretest–posttest control group approach.A total of 86 adolescent girls were recruited and divided equally into intervention and control groups at SMK Negeri 11 Semarang.The intervention group received the 8,000 HPK module for seven days, while the control group received standard leaflet-based education.Data were collected using validated and reliable questionnaires on knowledge and self-efficacy and analyzed using the Wilcoxon Signed Rank Test and Mann–Whitney Test. Results: A significant increase was observed in the intervention group’s knowledge (p = 0.000, Δ = 4.00) compared to the control group (Δ = 2.00). Similarly, self-efficacy improved significantly in the intervention group (p = 0.000) with a Cohen’s d effect size of 14.00, indicating a very large effect. Conclusion: Youth classes using the 8,000 Days of Life (HPK) module effectively enhanced adolescents’knowledge and self-efficacy in stunting prevention compared to standard educational media. Keywords: youth class; 8,000 days of life module; knowledge; self-efficacy; stunting prevention